Analysis of Intestinal Metaplasia Without Dysplasia in the Urinary Bladder Reveal Only Rare Mutations Associated With Colorectal Adenocarcinoma. Issue 10 (November 2020) - Amin, Ali; Murati-Amador, Belkiss; Lombardo, Kara A.; Jackson, Cynthia L.; Grada, Zakaria; Palsgrove, Doreen N.; Matoso, Andres
Abstract : Intestinal metaplasia (IM) is a rare finding in urinary bladder specimens. It is unclear whether IM without dysplasia is a precursor of malignancy in the urinary system. We retrospectively selected 9 cases of IM of bladder (1 case harboring high-grade dysplasia), and performed mutation analysis for genes frequently mutated in colon cancer including BRAF, APC, KRAS, MET, NRAS, PIK3CA, CTNNB1, FBXW7, and TP53 using validated clinical tests. Control groups included 7 colonic tubular adenomas, 10 high-grade papillary urothelial carcinomas. One IM case revealed an APC mutation and another showed an NRAS mutation. Among the tubular adenomas cases, 6 of 7 (85.7%) harbored KRAS mutations and 3 of 7 (42%) APC mutations. Among urothelial carcinomas cases, 1 revealed a KRAS mutation, 2 had PIK3CA mutations, and all cases were negative for APC mutations. Clinical follow-up for the IM patients was available with a median follow-up of 70 months. One patient—without any mutation in the genes investigated—developed invasive bladder adenocarcinoma with intestinal differentiation with metastasis to the liver and lung. Neither of the 2 patients harboring mutations developed any malignancy. In conclusion, a minority of cases with IM without dysplasia bear mutations in the genes commonly associated with colonic adenocarcinoma, suggesting a premalignant potential for such lesions possibly following the classic multistep chromosomal instability pathway of carcinogenesis. A larger cohort of patients with longer follow-up is needed to better establish whether close follow-up is warranted for mutation-harboring IM of the bladder.